Power Control of Wind Turbine Based on Fuzzy Sliding-Mode Control - Tahir Khalfallah; Belfedal Cheikh; Allaoui Tayeb; Gerard Champenois (Institute of Advanced Engineering and Science, 2015)
This paper presents the study of a variable speed wind energy conversion system (WECS) using a Wound Field Synchronous Generator (WFSG) based on a Fuzzy sliding mode control (FSMC) applied to achieve control of active and reactive powers exchanged between the stator of the WFSG and the grid to ensure a Maximum Power Point Tracking (MPPT) of a wind energy conversion system. However the principal drawback of the sliding mode, is the chattering effect which characterized by torque ripple, this phenomena is undesirable and harmful for the machines, it generates noises and additional forces of torsion on the machine shaft. A direct fuzzy logic controller is designed and the sliding mode controller is added to compensate the fuzzy approximation errors. The simulation results clearly indicate the effectiveness and validity of the proposed method, in terms of convergence, time and precision.